ANALISIS MINATBERWIRAUSAHA FASHION PADA PESERTA DIDIK KELAS XII TATA BUSANA DI KOTA PONTIANAK - Agusteri, Weny; Buwono, Sri; Sutomo, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this research is to explain: (1) the entrepreneurial interest in fashion reviewed from intrinsic factors, (2) the interest in self- entrepreneurs in fashion reviewed from extrinsic factors, and (3) the most interest in self-entrepreneurship in fashion is from the most attractive fashion type of person. The method of this research used is descriptive method with qualitative research type, data collection method through interviews and documentation. The participant in this study are 27 trainess student of XII fashion class. The analysis of the validity of the data in this research uses triangulation with the data processing using Miles and Huberman models. The result of this research is the trainess XII fashion class are already showing a keen interest in entrepreneurship in fashion of intrinsic and extrinsic factors and the most attractive field of fashion is boutique compared to the other three areas of modiste, haute couture and convection